Historical Dictionary of the IMF - Humphreys, Norman (International Monetary Fund, 2000)
IMF economists work closely with member countries on a variety of issues. Their unique perspective on country experiences and best practices on global macroeconomic issues are often shared in the form of books on diverse topics such as cross-country comparisons, capacity building, macroeconomic policy, financial integration, and globalization.